2017
DOI: 10.1177/2042018817741852
|View full text |Cite
|
Sign up to set email alerts
|

Treating nonalcoholic fatty liver disease in patients with type 2 diabetes mellitus: a review of efficacy and safety

Abstract: All reviewed treatment options are safe for management of NAFLD in patients with T2DM but long-term histological improvements are minimal. TZDs are efficacious for resolution of NASH and improvements in fibrosis but long-term use is required to maintain these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Even though the studied cohort exhibited a high burden of metabolic comorbidities at the time of liver biopsy, drug therapy according to current guidelines on the management of hyperlipidaemia was only administered in roughly 50% of patients . This could in parts be related to concerns of drug‐induced liver injury as has been described in this class, but considering the high cardiovascular mortality of patients with NAFLD, this class of drugs should not be withheld and the safety concerns are low . One‐third of the cohort was diabetic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the studied cohort exhibited a high burden of metabolic comorbidities at the time of liver biopsy, drug therapy according to current guidelines on the management of hyperlipidaemia was only administered in roughly 50% of patients . This could in parts be related to concerns of drug‐induced liver injury as has been described in this class, but considering the high cardiovascular mortality of patients with NAFLD, this class of drugs should not be withheld and the safety concerns are low . One‐third of the cohort was diabetic.…”
Section: Discussionmentioning
confidence: 99%
“…33 This could in parts be related to concerns of drug-induced liver injury as has been described in this class, 34 but considering the high cardiovascular mortality of patients with NAFLD, 25 this class of drugs should not be withheld and the safety concerns are low. 35 One-third of the cohort was diabetic. Interestingly, the use of insulin in this cohort was high: 30% of the patients with diabetes type 2 were on some form of injectable insulin, mostly a combination of short and longacting compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In our small cohort with repeat biopsies, NAS and steatosis were stable or improved. Prior studies have suggested that treatment with insulin sensitizers such as metformin, rosiglitazone, or pioglitazone may help to improve NAFLD in type 2 diabetes . The histologic stability or improvement demonstrated by our subjects provides further support to the previous suggestion that metformin may exert beneficial effects on NAFLD that are unrelated to its glycemic actions, and further study is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin, an indirect AMPK activator, is being considered a possible option, 36 current evidence however is insufficient to recommend metformin against NAFLD. 37 Metformin primarily acts by decreasing mitochondrial capacity (leading to AMP accumulation activating AMPK) and therefore may not be an ideal exercise mimetic, as evinced through blunted exercise effects in prediabetic patients on metformin. 38 AICAR, on the other hand, has been trialed particularly in myocardial ischemia, with some, but not all, studies documenting ischemic protection including a reduced mortality.…”
Section: Discussionmentioning
confidence: 99%